Delayed matching to sample task 48: assessment of malingering with simulating design - Nikolai, T; Cechova, K; Bukacova, K; Fendrych Mazancova, A; Markova, H; Bezdicek, O; Hort, J; Vyhnalek, M (Neuropsychology, development, and cognition. Section B, Aging, neuropsychology and cognition, 2021)
The results of neuropsychological tests may be distorted by patients who exaggerate cognitive deficits. Eighty-three patients with cognitive deficit [Amnestic Mild Cognitive Impairment (aMCI), n = 53; Alzheimer's disease (AD) dementia, n = 30], 44 healthy older adults (HA), and 30 simulators of AD (s-AD) underwent comprehensive neuropsychological assessment. Receiver Operating Characteristic (ROC) analysis revealed high specificity but low sensitivity of the Delayed Matching to Sample Task (DMS48) in differentiating s-AD from AD dementia (87 and 53%, respectively) and from aMCI (96 and 57%). The sensitivity was considerably increased by using the DMS48/Rey Auditory Verbal Learning Test (RAVLT) ratio (specificity and sensitivity 93% and 93% for AD dementia and 96% and 80% for aMCI). The DMS48 differentiates s-AD from both aMCI and AD dementia with high specificity but low sensitivity. Its predictive value greatly increased when evaluated together with the RAVLT.
Keywords: simulování; mild cognitive impairment; Aged; symptom validity testing; neuropsychological assessment; Cognition Disorders; kognitivní poruchy; Humans; neuropsychologické testy; Neuropsychological Tests; senioři; lidé; Alzheimer Disease; Alzheimer’s disease; kognitivní dysfunkce; Alzheimerova nemoc; Cognitive Dysfunction; Malingering